Nursing strategies in antimicrobial stewardship in the hospital environment: a qualitative systematic review - Flavia Giron Camerini; Tonia Lourenço Cunha; Cintia Silva Fassarella; Danielle de Mendonça Henrique; Juliana Gerhardt Soares Fortunato (BMC, 2024)
Abstract Background Antimicrobial resistance has become one of the world's most important public health problems. Accordingly, nursing strategies to manage antimicrobials in hospital environments are fundamental to promoting patient health. The aim of this study was to summarise the best evidence available on nursing strategies for the safe management of antimicrobials in hospital environments. Methods This qualitative systematic review used meta-aggregation in accordance with the recommendations of the Joanna Briggs Institute. The protocol was registered in the data base of the Prospective Register of Systematic Reviews under No. CRD42021224804. The literature search was conducted, in April and May 2021, in the following data bases and journal repositories: Latin American and Caribbean Health Sciences Literature (LILACS) via the Virtual Health Library (VHL), Medical Literature Analysis and Retrieval System on-line (Medline) via PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Scientific Electronic Library Online (SciELO) and Excerpta Medica Database (EMBASE). The findings of each study were summarized and the results were meta-aggregated in JBI SUMARI software. Results The search resulted in a total of 447 studies and, after selection, the review included 26 studies, in which 42 nursing strategies were identified. The strategies were first categorised as care- or stewardship-related and then into the subcategories: Screening, Administration, Monitoring and Discharge, Nursing Team, Multi-professional Teams, Patients and Institutional Leadership. The 42 strategies were meta-aggregated and represented in flow diagrams. The best evidence was synthesized related to nursing strategies in the safe management of antimicrobials in the hospital environment. Conclusions Nurses play an indispensable function in antimicrobial stewardship in the hospital environment, because they work directly at the core of safe patient care. Significant contributions by nursing towards reducing antimicrobial resistance were found in care-related practice, education activities, research and policy.